Implementasi Pengamanan Data Menggunakan Kombinasi Algoritma Kriptografi AES-256 dan Teknik Steganografi End-of-File (EOF) Pada Media Citra Digital - Jakbar Ali Harahap; Muhammad Aulia; Muhammad Rasyya Alfarisi; Soty Sohaimi (JIKUM: Jurnal Ilmu Komputer, 2026)
In the contemporary digital landscape, the security and confidentiality of information exchange have emerged as paramount concerns due to the increasing sophistication of cyber threats. This study proposes an integrated security framework through the development of "PrivaSel," a hybrid application that synergizes advanced cryptography and steganography to achieve dual-layer protection. The system employs the Advanced Encryption Standard (AES) with a robust 256-bit key length, implemented in Cipher Block Chaining (CBC) mode to ensure high-level data confidentiality and resistance against frequency analysis attacks. Key derivation is further strengthened using the PBKDF2 algorithm with 100,000 iterations and a random salt to mitigate brute-force vulnerabilities. For the covert layer, the system utilizes the End-of-File (EOF) steganography technique, which embeds encrypted payloads into diverse container media including images and videos without altering the spatial pixel data. Developed using a Python-based FastAPI backend and a responsive HTML5/Tailwind CSS frontend, the application facilitates seamless asynchronous processing. Empirical testing through histogram analysis confirms that the EOF method maintains absolute visual integrity, yielding a Mean Squared Error (MSE) of 0.00 and an infinite Peak Signal-to-Noise Ratio (PSNR). The results demonstrate that while the file size increases linearly relative to the payload and metadata overhead, the hidden information remains imperceptible to statistical analysis and can be flawlessly retrieved only with the authorized password, providing a reliable solution for secure multi-file data transmission.